Level of physical activity in chronic kidney patients undergoing hemodialysis - Lessa, Larissa de Holanda (2018)
Introduction: Sedentarism is one of the factors that influence the health of patients undergoing hemodialysis (HD). Objective: To identify the level of physical activity of patients with chronic kidney disease (CKD) submitted to the HD. Methods: This is a descriptive cross-sectional study. The following variables were considered in the present study: age, gender, time of HD and level of physical activity by means of applying the International Physical Activity Questionnaire (IPAQ), short version. Patients were classified as very active, active, irregularly active or sedentary. Results: Regardless of the time of HD, in general, a level of sedentarism ranging from 46.9 to 62.2% was observed. Considering all times of HD (from 1 to > 48 months), 55.1% of sedentary patients were observed. Conclusion: The majority of patients with CKD undergoing HD present a level of physical activity below the recommended, classified as sedentary according to IPAQ.